Why are the media so soft on Circle?. (8th August 2012) - Hawkes, Nigel
Abstract : Recent coverage has uncritically praised Hinchingbrooke, the first privately managed NHS hospital, but was it more a public relations coup than reality, asks Nigel Hawkes, as the company seeks to avoid insolvency